VILLAGE HOUSEHOLD FOR SMALL HPPS CURRENT TO DO CONDITION IN UZBEKISTAN - Topvoldiyev Nodirbek Abdulhamid o‘g‘li,; Shavkatbekov Husanboy, (Лучшие интеллектуальные исследования, 2024)
Abstract. In this article, the guidelines for the application of small hydropower plants to agriculture were considered.